Genetic organization of alpha-bungarotoxins from Bungarus multicinctus (Taiwan banded krait): evidence showing that the production of alpha-bungarotoxin isotoxins is not derived from edited mRNAs. - Chang, L (1999)
Two genomic DNAs with a size of approximately 2.8 kb, isolated from the liver of Bungarus multicinctus (Taiwan banded krait), encode the precursors of the long neurotoxins, alpha-Bgt(A31) and alpha-Bgt(V31), respectively. Both genes share virtually identical overall organization with three exons separated by two introns, which were inserted in the same positions in the coding regions of the genes. Moreover, their nucleotide sequences share approximately 98% identity. This result indicates that the two genes co-exist in the genome of B.multicinctus, and probably arose from gene duplication. The exon/intron structures of the alpha-Bgt genes were essentially the same as those reported for the short neurotoxins. This reflects that the long and short neurotoxins should share a common evolutionary origin. Comparative analyses on long neurotoxin and short neurotoxin genes showed that the protein coding regions of the exons were more diverse than the introns except for the signal peptide domain. This implies that the protein coding regions of the neurotoxins may have evolved via accelerated evolution. PCR amplification of venom gland cDNA mixtures revealed that only two amino acid sequences corresponding to alpha-Bgt(A31) and alpha-Bgt(V31) could be deduced from the cDNAs. The results of chromatographic analyses and protein sequencing again emphasized the view that, with the exception of alpha-Bgt(A31) and alpha-Bgt(V31), no other alpha-Bgt isotoxins with amino acid substitutions were present in B.multicinctus venom. In contrast to the proposition of Liu et al. ( Nucleic Acids Res., 1998,26, 5624-5629), our findings strongly suggest that each alpha-Bgt isotoxin is derived from the respective gene, and that alpha-Bgt RNA polymorphism does not originate from one single, intronless gene by the mechanism of RNA editing.